(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2020)
The hybrid concept that develops in urban community settlements in an unplaning manner has led to various forms of settlement patterns that are adapted to social, economic and environmental conditions. This hybridity condition is potential for more innovative settlement consolidation efforts. This research was conducted to examine the quality of the hybridity formed in urban village settlements in Sindulang Satu Village, Manado, and to find the consolidation principle of settlement patterns by developing hybridity values at the site location. The quality of the hybridity was examined based on the perspective of programming hybrid, operational hybrid and spatial hybrid. This study used a qualitative research method, with modeling and experimental simulation technique approach. The analysis of settlement space performance was done by statistical calculations and graphical analysis using space syntax method. The research data was obtained using questionnaire, interviews and observations methods of samples that met the criteria of purposive sampling. The results of this study showed the potential of the hybridity in site locations with good quality, so that it became a consideration in formulating the principle of settlement pattern consolidation to increase site hybridity.